TEACHING ENGINEERING FOR FOREIGN STUDENTS - Eduard G. Krylov (Высшее образование в России)
The paper discusses psychological, pedagogical, and organizational features of teaching engineering for foreign students at Russian technical universities. It is shown that the modern educational technologies can enhance the effectiveness of teaching.